2022
DOI: 10.1002/jwmg.22146
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional landscape connectivity for lesser prairie‐chickens in the Sand Shinnery Oak Prairie Ecoregion

Abstract: The lesser prairie-chicken (Tympanuchus pallidicinctus) is a species of conservation concern on the Southern High Plains of Texas and New Mexico, USA. Because fragmentation and isolation have increased since pre-settlement, dispersal through this heterogeneous landscape may be constrained, with serious implications for conservation and management of this species. Our objectives were to quantify landscape connectivity for lesser prairie-chickens within a patch network of potentially isolated leks (breeding disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Analysis of vegetation measurements from the Cimarron and Comanche National Grasslands as well as native rangelands suggests that native grasslands are not currently providing resources for lesser prairie‐chicken occupancy, including vegetation cover and appropriate plant communities (Berigan et al., 2022 ). Outside of our study area, however, native grassland does provide vegetation cover and plant communities amenable to lesser prairie‐chicken occupancy (Short‐Grass Prairie/CRP Mosaic Ecoregion, Kraft, 2016 ; Mixed‐Grass Prairie Ecoregion, Lautenbach, 2017 ; Sand Shinnery Oak Prairie Ecoregion, Schilder et al., 2022 ). It is likely that heterogenous lesser prairie‐chicken habitats, including both CRP and native grassland, can facilitate lesser prairie‐chicken dispersal movements provided that the grasslands have appropriate vegetation composition and structure for lesser prairie‐chicken occupancy (habitat requirements detailed in Hagen et al., 2004 ; Haukos & Zavaleta, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of vegetation measurements from the Cimarron and Comanche National Grasslands as well as native rangelands suggests that native grasslands are not currently providing resources for lesser prairie‐chicken occupancy, including vegetation cover and appropriate plant communities (Berigan et al., 2022 ). Outside of our study area, however, native grassland does provide vegetation cover and plant communities amenable to lesser prairie‐chicken occupancy (Short‐Grass Prairie/CRP Mosaic Ecoregion, Kraft, 2016 ; Mixed‐Grass Prairie Ecoregion, Lautenbach, 2017 ; Sand Shinnery Oak Prairie Ecoregion, Schilder et al., 2022 ). It is likely that heterogenous lesser prairie‐chicken habitats, including both CRP and native grassland, can facilitate lesser prairie‐chicken dispersal movements provided that the grasslands have appropriate vegetation composition and structure for lesser prairie‐chicken occupancy (habitat requirements detailed in Hagen et al., 2004 ; Haukos & Zavaleta, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the maximum distance each individual moved from lek of capture averaged 5.1 km (range: 0.4–17.2 km), indicating that marked lesser prairie‐chickens in this study were capable of making long‐distance movements. At a landscape scale, wind energy has the potential to reduce connectivity between leks, and may impact population viability (Peterson et al 2020, Schilder et al 2022). However, as our results suggest, habitat connectivity is likely to be landscape context dependent, and given the extensive cultivated cropland in the interior of the facility, we cannot conclude that marked individuals would have moved through the area absent turbines.…”
Section: Discussionmentioning
confidence: 99%
“…Lesser prairie-chickens (LPC) are managed in four discreet ecoregions across their distribution: (1) Short-Grass Prairie/Conservation Reserve Program (CRP); (2) Sand Sagebrush Prairie; (3) Mixed-Grass Prairie, and (4) SSOP (from the Lesser Prairie-Chicken Interstate Working Group Range-Wide Management Plan (RWP) [13,14]). LPC require sand shinnery oak to persist in the SSOP ecoregion [15][16][17][18][19][20][21]. Lesser prairie-chickens lek, nest, and raise broods in sand shinnery oak habitats [18,20,[22][23][24][25].…”
Section: Remote Sensing Of Lpc Habitat In the Ssopmentioning
confidence: 99%
“…Anthropogenic effects on landscapes and vegetation communities that support lesser prairie-chicken extend beyond outright loss of habitat. Lesser prairie-chickens avoid anthropogenic features when nesting [18,[49][50][51]; their home ranges are often constrained within areas without human structures [52,53]; their survival varies among areas with disproportionate anthropogenic development [54,55]; and contemporary evidence suggest functional connectivity may be limited in areas with wind farms and other development [21]. Our assessment adds to the weight of the evidence that anthropogenic development within lesser prairie-chicken ranges corresponds to long-term population declines.…”
Section: Implications Of Lpc Habitat Conservationmentioning
confidence: 99%
See 1 more Smart Citation